Perseguindo a Maturidade nas Organizações. Dimensões Para o Desenvolvimento Humano Integral - Vitor Hugo Klein Jr (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2012)
Maturity has been little addressed by organization studies. This is, however, a relevant issue, especially when considering the various criticisms against the manager profession on the harmful consequences of it to stakeholders and to society, as exemplified by scandals and systemic crises. This theoretical essay aims to present a three-dimensional matrix of maturity developed from an interdisciplinary basis. The conceptual matrix addresses maturity through three dimensions: individual/social, psychological and political. It is advocated that the achievement of maturity involves the various capacities of the individual to face his internal and external reality, as well as his ability to act in the world. The analysis here developed offers the following conclusions: (a) maturity is not only dependent on the individual but on the relationships established in group as well; (b) the phenomenon has unconscious origins, which may determine part of behavior and relationships in groups; and (c) maturity is intimately related to balanced, reflexive and participatory human action.